1974
DOI: 10.1086/225763
|View full text |Cite
|
Sign up to set email alerts
|

"New Princes" for Old? The Large Corporation and the Capitalist Class in Chile

Abstract: Fecha de recepción: 18 de septiembre del 2015 Fecha de aceptación y versión final: 9 de febrero del 2016 RESUMEN: Enredar a las elites empresariales es un llamamiento a estudiar las redes de las personas y organizaciones que dirigen y controlan las grandes empresas. Este artículo analiza y visibiliza a las elites empresariales en México, Chile, Perú y Brasil mediante el análisis de redes de interlocking directorates y propiedad entre las grandes empresas. Los resultados contribuyen a teorías y debates sobre la… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0
2

Year Published

1976
1976
2019
2019

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 57 publications
(13 citation statements)
references
References 8 publications
0
11
0
2
Order By: Relevance
“…At the hub of the system were the banking institutions which had links with manufacturing enterprises and other businesses, secured through interlocking directorates, kinship relations or both (Lagos 1961). Close-tied family control was common as Zeitlin et al (1974) found in a study which showed the majority of Chilean managerial-controlled firms were owned by one or two families and their associates. Effectively, a small core of elite business families in Chile ran the most of the economy.…”
Section: The Chilean Case Study: the Historical Development Of A Busimentioning
confidence: 92%
“…At the hub of the system were the banking institutions which had links with manufacturing enterprises and other businesses, secured through interlocking directorates, kinship relations or both (Lagos 1961). Close-tied family control was common as Zeitlin et al (1974) found in a study which showed the majority of Chilean managerial-controlled firms were owned by one or two families and their associates. Effectively, a small core of elite business families in Chile ran the most of the economy.…”
Section: The Chilean Case Study: the Historical Development Of A Busimentioning
confidence: 92%
“…Behind markets, practice theorists point to connections and communities. In many regions, the scope of the firm is determined by "kineconic" relations rather than pure market rationality, as, for example, with the kinship networks that govern the diversification strategies of Chilean conglomerates (Zeitlin et al 1974). The most valuable company in the world, Aramco, is controlled by a royal family, the House of Saud (Baxter and Said 2016): state and business are connected by blood.…”
Section: From Theory To Practicementioning
confidence: 99%
“…Under capitalism, with its dictum of accumulation, corporations should change groups whenever short-term pro®t could be improved. This is particularly emphasized in theories containing the assumption of class consciousness and the creation # Blackwell Publishers Ltd 1998 SVEN-OLOF COLLIN of value congruence, or common order of preference, in the capitalist class (Nichols, 1969;de Vroey, 1975;Zeitlin et al, 1975). In such terms, there are no liaisons, loyalties, speci®cities or inertia, such as the costs of shifting BGs would involve, that create long-term relationships.…”
Section: Capitalmentioning
confidence: 99%